2015
DOI: 10.1007/s12630-015-0463-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of light versus deep propofol sedation for elective outpatient colonoscopy: recall, procedural conditions, and recovery

Abstract: A randomized controlled trial of light versus deep propofol sedation for elective outpatient colonoscopy: recall, procedural conditions, and recovery Une étude randomisée contrôlée sur la sédation légère vs profonde au propofol pour la colonoscopie non urgente en ambulatoire: le souvenir, les conditions entourant l'intervention et la récupération sedation; P \ 0.0001). The incidence of recall was 12% in the light sedation group and 1% in the deep sedation group. The risk difference for recall was 0.11 (90% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
1
34
0
2
Order By: Relevance
“…Emergency patients suffered more intra-operative significant unplanned events (20.6% vs 14.4%; P ¼ 0.003) and 30-day mortality (6.0% vs 0.2%; P <0.0001) than elective patients. Time to death was not significantly different in elective and emergency patients who died (13 [0-28] days in emergency patients vs 11 [10][11][12][13][14][15][16][17][18] days in elective patients; P ¼ 0.49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency patients suffered more intra-operative significant unplanned events (20.6% vs 14.4%; P ¼ 0.003) and 30-day mortality (6.0% vs 0.2%; P <0.0001) than elective patients. Time to death was not significantly different in elective and emergency patients who died (13 [0-28] days in emergency patients vs 11 [10][11][12][13][14][15][16][17][18] days in elective patients; P ¼ 0.49).…”
Section: Resultsmentioning
confidence: 99%
“…Events with a frequency of nine or more (0.3%) would have 95% confidence intervals (CI) where the lower limit was greater than 0.1%. 13 Based on published results 14 and our recent trial, 15 this sample size was thought to be sufficient for robust estimates of most intra-procedure events.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…These observations are consistent with studies using similar sedation regimens. 22 We did not identify significant modifiable predictors of hypotension in this study. While we found that lower VAS scores for thirst after infusion were associated with greater odds of hypotension, given the multiple factors tested, this could be a random relationship.…”
Section: Discussionmentioning
confidence: 54%
“…5 Depth of sedation was measured using the bispectral electroencephalographic (EEG) index (i.e., bispectral index [BIS]) aimed at a BIS value of 70-80 or \ 60 for ''light'' and ''deep'' sedation, respectively. The primary outcome was unintentional recall of the procedure.…”
mentioning
confidence: 99%
“…rapportent un essai randomisé d'équivalence comparant la sédation profonde à la sédation légère en utilisant une perfusion de propofol à concentration cible chez 199 patients ambulatoires subissant une colonoscopie. 5 La profondeur de la sédation a été mesurée au moyen d'un indice encéphalographique (EEG) bispectral (c'est-à-dire, l'indice bispectral [BIS]) visant une valeur de 70 à 80 ou\ 60 pour, respectivement, une sédation « légère » ou une sédation « profonde ». Le critère d'évaluation principal était la mémoire involontaire de la procédure.…”
unclassified